A Study of Patients with Primary Mediastinal Germ Cell Tumors Treated Using Multimodal Therapy. (28th May 2017) - Tanaka, Yutaro; Okamura, Takehiko; Nagai, Takashi; Kobayashi, Daichi; Kobayashi, Takahiro; Akita, Hidetoshi; Moritoki, Yoshinobu; Yasui, Takahiro
Abstract : Objectives . Primary mediastinal germ cell tumors (PMGCTs) are rare, which often makes them difficult to treat. Herein, we examined patients with PMGCTs who underwent multimodal treatment. Methods . We examined 6 patients (median age: 25 years, range: 19–27 years) with PMGCTs who underwent multimodal treatment between April 2001 and March 2015. Three patients had seminomas, 2 patients had yolk sac tumors, and 1 patient had choriocarcinoma. The median observation period was 32.5 months (range: 8–84 months). Results . Three of the 6 patients received initial operation followed by 3-4 courses of chemotherapy (bleomycin, etoposide, and cisplatin (BEP) or etoposide and cisplatin (EP)). One patient developed multiple lung metastases 17 months after surgery; received salvage chemotherapy with vinblastine, ifosfamide, and cisplatin; and achieved complete remission. The remaining 3 patients received initial BEP and EP chemotherapy. Multiple lung metastases and supraclavicular lymph node metastases were detected in 2 of these patients at the initial diagnosis. The patients underwent resections to remove residual tumor after treatment, and no viable tumor cells were found. Conclusions . Reliable diagnosis and immediate multimodal treatments are necessary for patients with PMGCTs. The 6 patients treated in our hospital have never experienced recurrence after the multimodal treatment.